Management of Student Development on The Impact of Smartphones Through the Role of Parents During the Pandemic - Farid Wajdi; Edi Wahyono; Asmani Arif (Universitas Negeri Makassar, 2021)
The purpose of the study was to determine the development of students during the pandemic on the impact of using smartphones through the role of parents in managing their children at home. This research is a type of quantitative research through an experimental approach. The data analysis technique used descriptive statistical analysis. The sample of this study was 6th-grade elementary school students with a population of 75 students. The sampling technique in this study is a simple random sampling technique. The results showed that students who took part in learning during the pandemic using smartphones without the role of their parents resulted in negative behaviors, such as addiction to online games, playing more than studying, and uttering bad words from their mouths. Meanwhile, students who take part in learning during the pandemic using smartphones through the role of parents have a good impact on student development, such as the use of smartphones for learning needs, and the lack of dirty words. The novelty of this study is the importance of the role of parents in educating students about the use of smartphones during the pandemic. The reason is that the learning process is mostly done online due to the Covid-19 pandemic.